Screening of PAH Common Mutations in Chinese Phenylketonuria Patients Using iPLEX MALDI-TOF MS - Yan, Yousheng (ACS Omega, 2020)
[Image: see text] Phenylketonuria (PKU) is caused by phenylalanine hydroxylase (PAH) gene variants. Previous research has identified some PAH mutation hotspots in Chinese patients with PKU. In this study, we introduce a novel MassArray panel for screening the 29 common PAH gene mutations in Chinese patients using iPLEX MALDI-TOF MS. 105 Patients with PKU and known PAH gene mutations were genotyped using this MassArray panel. All of the 29 mutations screened were detected, and MassArray panel results were consistent with those obtained by Sanger sequencing. Fifty patients newly diagnosed with PKU were recruited in the double-blind experiment. PAH gene variants were detected in these 50 patients using the MassArray panel, and the results were verified with Sanger sequencing and Multiplex Ligation-dependent Probe Amplification (MLPA) methods. Our results show that the mutation detection rate using the MassArray panel with 29 mutations is 74% (95% CI, 65–83%), and the clinical genetic diagnosis rate is 54% (95% CI, 40–68%). This panel can be used as a high throughput, low cost, and rapid method for screening and diagnosing PAH gene mutations. The establishment of this approach provides proof-of-concept for future large-scale PAH mutation carrier screening in areas with high rates of PKU.